Enterprise data governance : reference & master data management, semantic modeling - Bonnet, Pierre (London : ISTE ; Hoboken, NJ : Wiley, 2010)
In an increasingly digital economy, mastering the quality of data is an increasingly vital yet still, in most organizations, a considerable task. The necessity of better governance and reinforcement of international rules and regulatory or oversight structures (Sarbanes Oxley, Basel II, Solvency II, IAS-IFRS, etc.) imposes on enterprises the need for greater transparency and better traceability of their data. All the stakeholders in a company have a role to play and great benefit to derive from the overall goals here, but will invariably turn towards their IT department in search of the answ.
A company and its data -- Strategic aspects -- Taking software packages into account -- Return on investment -- MDM maturity levels and model-driven MDM -- Data governance functions -- Organizational aspects -- The semantic modeling framework -- Semantic modeling procedures -- Logical data modeling -- Organization modeling -- Technical integration of an MDM.
Includes bibliographical references (pages 285-286) and index.
Print version record.
English.
John Wiley and Sons
Keywords: Data protection; Protection de l'information (Informatique); Data protection